Socioeconomic Status, Race, and Public Support for School Integration - Deven Carlson; Elizabeth Bell (SAGE Publishing, 2021)
Polling data routinely indicate broad support for the concept of diverse schools, but integration initiatives-both racial and socioeconomic-regularly encounter significant opposition. We leverage a nationally representative survey experiment to provide novel evidence on public support for integration initiatives. Specifically, we present respondents with a hypothetical referendum where we provide information on two policy options for assigning students to schools: (1) a residence-based assignment option and (2) an option designed to achieve stated racial/ethnic or socioeconomic diversity targets, with respondents randomly assigned to the racial/ethnic or socioeconomic diversity option. After calculating public support and average willingness-to-pay, our results demonstrate a clear plurality of the public preferring residence-based assignment to the racial diversity initiative, but a near-even split in support for residence-based assignment and the socioeconomic integration initiative. Moreover, we find that the decline in support for race-based integration, relative to the socioeconomic diversity initiative, is entirely attributable to White and Republican respondents.